Dual-crosslinked hydrogel microwell system for formation and culture of multicellular human adipose tissue-derived stem cell spheroids. Issue 20 (18th April 2016) - Jeon, Oju; Marks, Robyn; Wolfson, David; Alsberg, Eben
Abstract : A novel biodegradable, biocompatible alginate-PEG hydrogel microwell system was developed with tailorable microwell physical and biochemical properties to control the uniform formation and behavior of three-dimensional multicellular human adipose tissue-derived stem cell spheroids. Abstract : Three-dimensional (3D) multicellular spheroids of human adipose tissue-derived stem cells (hASCs) are an attractive system for basic science studies and tissue engineering applications, as they can resemble cellular condensations present in developmental and healing processes. The purpose of this study was to engineer a hydrogel-based microwell platform by capitalizing on the differential swelling behavior of micropatterned dual-crosslinked oxidized, methacrylated alginate (OMA)/multi-arm polyethylene glycol (PEG) hydrogels for rapid formation of uniform multicellular hASC spheroids with controllable size and evaluation of the capacity of the system to be used to drive osteogenic differentiation of the spheroids. By changing the micropattern size, the size of the hydrogel microwells was easily controllable. Microwell-seeded hASCs generated spheroids of relatively uniform size and high cell viability. hASC spheroids exhibited rapid mineralization in osteogenic media, which was faster than that of conventional two-dimensionally cultured hASCs. This new hydrogel microwell system has great potential for controlled multicellular spheroid formation and defined signal presentation from the hydrogel material to the cell aggregates to regulate tissue formation.